The return - Hislop, Victoria, 1959- (Headline, 2009)
Beneath the majestic towers of the Alhambra, Granada's cobbled streets resonate with music and secrets. Sonia Cameron knows nothing of the city's shocking past; she is here to dance. But in a quiet café, a chance conversation and an intriguing collection of old photographs draw her into the extraordinary tale of Spain's devastating civil war.